Users' motivation to participate in crowdsourcing: a South African case study - Machine, David (Department of Information Systems, 2016)
Growth in online communities has generated a new labour pool. Organisations are using Web 2.0 tools to tap into this online labour pool, with one approach being 'crowdsourcing'. People from different geographical destinations can now work for organisations that are thousands of kilometres from them. Organisations face a huge task of attracting a large crowd of workers that can actively contribute answers to their business problems. Knowing what motivates users and how to keep them actively participating over a long period of time is therefore crucial. This study explores how organisational, individual, technical and social factors affect users' motivation to participate in crowdsourcing projects. A single case study using a crowdsourcing company based in South Africa was used. The crowdsourcing company uses crowdsourcing for monitoring online activities on behalf of other companies for online conversations on social platforms such as Twitter, Facebook, news articles, blog posts and listings on directory sources such as Gumtree or property listings. A qualitative study on thirteen participants was conducted through semi - structured Skype interviews. A conceptual model is presented based on the research findings. Besides re - establishing a number of factors which affect motivation to participate in crowdsourcing, the study established new emergent factors which had not been common in previous studies. The factors include authenticity of the whole crowdsourcing project, mentorship of new users by seasoned users, flexibility of technological tools in meeting users' expectations and feedback. Practical lessons drawn from the study could help crowdsourcing practitioners understand users' motivation to participate in crowdsourcing and how to ensure a conducive environment for crowd participation and hence quality output. Additionally the study could inform key considerations when implementing a crowdsourcing project in an organisation.